Cancerous esophageal stenosis before treatment was significantly correlated to poor prognosis of patients with esophageal cancer: a meta-analysis - Deng, Han-Yu; Alai, Guha; Luo, Jun; Li, Gang; Zhuo, Ze-Guo; Lin, Yi-Dan (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Cancerous esophageal stenosis encountered during endoscopic ultrasonography before treatment was observed in about 30% of esophageal cancer patients. Since the pT stage in TNM classification measures only the depth of infiltration but not the growth to esophagus, it is interesting to know whether tumor growth into the esophagus (and eventual stenosis) is of added value in prognostic assessment. However, the impact of esophageal stenosis on survival of esophageal cancer patient remains unclear. Therefore, we conducted a meta-analysis focusing on current topic for the first time. Methods: A systematic literature search in PubMed and EMBASE was conducted to identify relevant studies up to 14 March 2018. Data of 5-year overall survival (OS) was extracted and analysed. Results: A total of five cohort studies consisting of 1,282 patients (278 patients with cancerous esophageal stenosis before treatment and 1,004 patients without) with esophageal cancer treated with surgery, chemoradiotherapy, or palliative therapy were included for analysis. Meta-analysis showed that patients with esophageal stenosis had significantly lower 5-year OS [22.3% and 33.0%, respectively; risk ratio (RR) =1.21; 95% CI, 1.11–1.32; P